Education on Adolescent Reproductive Health at MTsS Thawalib Pesantren Padang - Melisa Yenti; Ahmad Hidayat; Bella Novriani; Arni Melati; Novia Larasati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Adolescents are faced with many problems related to reproductive health, so adolescents need to know to be able to face these challenges. However, the knowledge of adolescents in Indonesia is still low, especially in terms of ways to protect themselves against reproductive health risks, such as preventing unwanted pregnancies, sexually transmitted infections, and AIDS. The provision of education needs to be done to address adolescent reproductive health problems. Educational activities related to reproductive health at MTsS Pesantren Thawalib Padang have never been conducted. The students MTsS are the right target group to be able to provide information related to reproductive health. The objective of this service activity is to enhance students' understanding of reproductive health, enabling them to cultivate a positive and responsible approach when addressing the sexual and reproductive changes that transpire within them. The approach employed involves student outreach and the placement of informative posters in their dormitories. The augmentation in students' knowledge was assessed using a questionnaire consisting of 15 questions before and after the activity. Data analysis was conducted through a paired sample t-test, a statistical method that compares the means of two related groups to determine if there is a significant difference between them. After the activity was carried out, there was an increase in the average level of knowledge before (pre-test), 40.63 to 49.76 after (post-test), providing education with a p-value of 0.000. It can be concluded that there is an increase in knowledge after adolescent reproductive health education. It is hoped that students can access reproductive health information from the posters displayed on the dormitory walls.